Analisa Keamanan Web Server Terhadap Serangan Distributed Denial of Service Menggunakan Modevasive - Muhamad Dody Firmansyah (Telcomatics, 2021)
Development of information Web technology Service, especially on digital security, whether in the form of a website, is a very important aspect in terms of efforts to prevent unwanted things from happening, such as a team of hackers who often commit crimes in cyberspace with the phishing method, ddos ​​attacking, and various methods used. to commit cyber crimes on the internet. The most popular attack techniques are found, such as, Cross Site Scripting, Sql Injection, phishing and ddos ​​attacks. The most frequently used hacker attack technique is the Distributed about Denial of Service technique. After collecting a lot of evidence, knowing that Tehcnic Distributed Denial of Service is a hacked attack technique carried out by remote experts, the researcher found that the Web Server Security Analysis was not yet fully effective, it could be overcome by the Distributed Denial of Service attack. Based on the background description problems above, the authors are interested in conducting research using Modevasive.